2022
DOI: 10.1111/bjh.18379
|View full text |Cite
|
Sign up to set email alerts
|

Current and future therapies for haemophilia—Beyond factor replacement therapies

Abstract: Summary Some non‐factor products that work by facilitating the coagulation pathway (emicizumab) and blocking the anticoagulant pathway (fitusiran, concizumab and marstacimab) for patients with haemophilia (H) have been developed, and clinical trials using these products are currently ongoing. Prophylaxis using non‐factor products by subcutaneous administration provides marked reductions of bleeding episodes in patients with HA or HB, regardless of the presence of inhibitor. Emicizumab has already been approved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 87 publications
0
15
0
Order By: Relevance
“…The current minimization of bleeding by prophylaxis regimens, as shown in our cohort, aims to extend the assessment of treatment outcomes and value beyond the ABR and target joints [ 34 ]. Along this line, early signs/markers of joint damage, as well of more reliable functional and patient-reported outcomes (including treatment satisfaction, as reported in our study) should be identified, also considering innovative products recently introduced in or approaching clinical practice in hemophilia, i.e., non-replacement agents and gene therapy [ 2 , 3 ].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The current minimization of bleeding by prophylaxis regimens, as shown in our cohort, aims to extend the assessment of treatment outcomes and value beyond the ABR and target joints [ 34 ]. Along this line, early signs/markers of joint damage, as well of more reliable functional and patient-reported outcomes (including treatment satisfaction, as reported in our study) should be identified, also considering innovative products recently introduced in or approaching clinical practice in hemophilia, i.e., non-replacement agents and gene therapy [ 2 , 3 ].…”
Section: Discussionmentioning
confidence: 96%
“…Regular prophylaxis, i.e., the long-term administration of therapeutic products aimed at preventing bleeding, particularly joint hemorrhages, with their deleterious impact on muscle–skeletal status and quality of life, is currently recommended in patients with severe hemophilia A and B (i.e., congenital deficiencies of coagulation factor [F] VIII or IX < 1%) and in moderate patients (FVIII/FIX 1–5%) with a severe bleeding phenotype [ 1 ]. Unlike hemophilia A, for which the first ‘non-replacement’ product, subcutaneously administered, is also available [ 2 ], intravenous injections of replacement factor concentrates are the mainstay of prophylaxis in hemophilia B [ 3 ]. The introduction of extended half-life (EHL) recombinant FIX (rFIX) concentrates, with relevant improvements of pharmacokinetic (PK) properties compared with standard half-life (SHL) concentrates [ 4 ], allowed for prolonged dosing intervals (up to 14–21 days vs. 2–4 days) and factor trough levels higher than those previously achieved, increasingly recognized to be inadequate to prevent all (clinical and subclinical) bleeding and the progression of arthropathy [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…While Emi maintains the coagulability of PwHA at a constant, it seemed unlikely to foster the prothrombotic tendency of PwHA suffering from sepsis‐associated DIC. In phase 3 clinical trials (HAVEN study) and long‐term observations, two and three patients receiving high doses of activated partial complex concentrates (aPCC; > 100 IU/kg daily for ≥24 h) developed TEs and thrombotic microangiopathy (TMA) respectively 6,32 . Therefore, if DIC develops during Emi and aPCC concomitant therapy, thrombotic symptoms should be noted.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these molecules are already authorized in some countries and others are currently evaluated in clinical trials. All allow for a remarkable reduction of bleeding accidents and are administered subcutaneously 8 . Yet, although symptomatic joint bleeds are significantly reduced, no current therapy is able to suppress the risk of haemophilic arthropathy which persists and appears to be related to sub‐clinical micro‐bleeds 9 …”
Section: Introductionmentioning
confidence: 99%
“…All allow for a remarkable reduction of bleeding accidents and are administered subcutaneously. 8 Yet, although symptomatic joint bleeds are significantly reduced, no current therapy is able to suppress the risk of haemophilic arthropathy which persists and appears to be related to sub-clinical micro-bleeds. 9 Hemophilia gene therapy (HGT) has been designed with the aim of getting the patient's hepatocytes to produce of the missing clotting factor.…”
Section: Introductionmentioning
confidence: 99%